World war i - Willmott, H. P. ([S.l.] : Dorling Kindersley Publishers Ltd, 2008)
This is anniversary edition of this dynamic portrait of World War I. It is published to coincide with the 90th anniversary of the armistice, this dramatic account of World War I combines emotive photography with personal accounts to evoke both the futility and spirit of the Great War. Every aspect of World War I - sea, land and the home front - are explored giving you a complete picture of the conflict. Re-live major campaigns through timelines and examine the decisions and military actions which decided each outcome. Compelling eyewitness accounts of soldiers and civilians paint a vivid picture both of crucial battles and day-to-day routines. Plus, letters home and haunting war poetry highlight the most important aspect of 'the war to end all wars' - its appalling human cost. With a special anniversary guide to battlefield sites, memorials, cemeteries and visitor centres at Verdun, the Somme, Ypres and other locations commemorating the fallen of World War I.
Keywords: Military campaigns; World War (1914-1918)